Ronald S. Calinger, Leonhard Euler. Mathematical genius in the Enlightenment, Princeton, NJ: Princeton University Press, 2016, xvii+669 p, (ISBN 978-0-691-11927-4/hbk; 978-0-691-11927-4/ebook). - COBZAȘ, S. (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
As writes the author in the Preface, Leonhard Euler (1707-1783) ranks among the four greatest mathematicians of all time, the other three being Archimedes, Isaac Newton and Karl Friederic Gauss. Although there exist some previous books containing short biographies of Euler, this is the first detailed and comprehensive account on Euler's life, research, computations and professional interactions. The presentation was possible due to the almost completion of more than eighty large volumes of Euler's Opera Omnia.